Advancing Systemic Therapy in Chondrosarcoma: New Horizons - Ka Hou C. Li; Ashish Gulia; Florence Duffaud; Robin L. Jones (Oncology and Therapy)
Abstract The systemic treatment landscape for advanced and metastatic chondrosarcoma, a malignancy with limited responsiveness to conventional therapies, has always been notoriously challenging. While standard chemotherapy offers minimal benefits, certain subtypes, such as mesenchymal and dedifferentiated chondrosarcomas, have shown some response to systemic therapies initially developed for other sarcomas. Investigational strategies are focusing on molecular targets, including mutations in the isocitrate dehydrogenase gene (IDH), signaling pathways, such as hedgehog and death receptor 5 (DR5) and immune modulation. IDH mutations, notably found in conventional and dedifferentiated chondrosarcomas, have prompted the evaluation of IDH inhibitors, which have demonstrated promising efficacy in preclinical and early clinical trials, despite limited data in chondrosarcoma. Additionally, the hedgehog pathway, implicated in chondrosarcoma progression, has been targeted with inhibitors, although clinical translation has shown mixed results. Immunotherapy, including programmed cell death 1 (PD-1) checkpoint inhibitors and chimeric antigen receptor-T (CAR-T) cells, is also being investigated but faces challenges due to the immunosuppressive tumour microenvironment. Among new approaches, DR5 agonists such as INBRX-109 have shown single-agent efficacy, with minimal toxicity, opening possibilities for use in combination therapies to improve outcomes. Given the heterogenous and treatment-resistant nature of chondrosarcoma, we highlight the need for multi-omics and genetic profiling to guide personalized, combination therapies that target multiple carcinogenic pathways. The integration of multi-targeted approaches could enhance efficacy, address tumour heterogeneity, and overcome resistance, presenting a hopeful direction for systemic therapy in this challenging cancer. The investigation of combination regimens with IDH inhibitors, immunotherapy and DR5 agonists hold promise for transforming the management of advanced chondrosarcoma.